2019
DOI: 10.2147/mb.s200096
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge of, and attitudes toward, codes of ethics and associated factors among medical doctors in Addis Ababa, Ethiopia</p>

Abstract: Background: Ethics are moral principles that attempt to determine what is morally right and wrong in human action. Professional ethics have gained significance and focus from time to time, due to increased public awareness and advancements in science and technology. Since there is limited information in Ethiopia, this study provides information about knowledge of, and attitudes toward, codes of ethics. Objective: To assess knowledge of and attitudes toward codes of ethics and associated factors among medical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Furthermore, in Ethiopia, one study showed that only 30.4% of medical doctors adhered to the code of ethics [37] though 75.7% of medical doctors have good knowledge about code of ethics [38]. Non-adherence to professional ethics might lead to medication errors that cause harm to the patient, person who made the error, and/or healthcare system at large [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in Ethiopia, one study showed that only 30.4% of medical doctors adhered to the code of ethics [37] though 75.7% of medical doctors have good knowledge about code of ethics [38]. Non-adherence to professional ethics might lead to medication errors that cause harm to the patient, person who made the error, and/or healthcare system at large [39].…”
Section: Discussionmentioning
confidence: 99%
“…26,27,29,31,34,36,37,39,[42][43][44][45][46] Only two studies objectively measured the participants' understanding of codes. 47,50 Three studies provided results but did not outline how they measured knowledge of the codes at all. 33,35,48 Most professionals indicated they have read their codes or were at least aware they exist, but showed poor levels of self-evaluated awareness of their contents.…”
Section: Awareness Of the Codementioning
confidence: 99%
“…31,34,44 However, both studies, which used objective measurement instead, showed participants had a good knowledge of their code's contents. Tiruneh et al 47 used a multiple-choice quiz to demonstrate that 75% of doctors had good knowledge of their code and Whyte and Gajos 50 showed nurses could correctly distinguish statements from their code from false statements 77.5% of the time. Dunning et al 53 suggested that self-evaluated measures of knowledge may be an unreliable measure and could vary significantly from what the participants did know about their codes.…”
Section: Awareness Of the Codementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the doctors are familiar with codes of ethics. By increasing awareness of professionalism among them, their behavior can be changed (Tiruneh, 2019).…”
Section: Introductionmentioning
confidence: 99%